Abortion politics, women's movements, and the democratic state : a comparative study of state feminism - McBride, Dorothy E. (Gender and politics., 2001)
This volume examines the impact of women's movements on the policy making processes determining abortion laws. It comprises the results of a cross-national research project on abortion politics in 11 democratic states between the 1960s and 2000.